The determination of the selenium levels in blood and tissues in sheep experimentally poisoned with selenium - Ahmet Ateşşahin (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the changes in ihe selenium levels in blood and tissues in sheep experimentally poisoned with selenium. In the study, 25 Morkaraman sheep at the weight of 50-55 kg were used Selenium was given orally at the doses of 1. 2. 3 and 4 mg/kg and intramuscularly at the doses of 0.1. 0.2. 0,4 and 0.6 mg/kg. Blood samples were laken Irom v.jugularis following the oral and intramuscularly application of selenium at 1. 3, 6, 9. 12, 18, 24, 48. 72, 120. 168, 240, 360, 480. 600th hours; and at 10, 20. 30th min. 1. 3, 6, 9, 12, 24. 48. 72. 120. 168. 240th hours, respectively. Selenium was intramuscularly given at the dose of 0.6 mg/kg and then tissue samples were bbtained at 1/2. 1, 3, 9 and 24th hours by decapitation of sheep. The blood selenium levels started (o increase at 1st hour and observed to reach to the maximum levels at 18th hours in all doses of selenium given orally. Then, the selenium levels were determined to gradually decrease to the near levels ol control groups at 360th hours at doses 1 and 2 mg/kg, and 600th hours at doses 3 and 4 mg/kg. The selenium levels of blood samples started lo increase in all doses at 10th min following the administration of selenium intramuscularly and reached to the maximum levels at 20th min at the doses of 0,1 and 0.2 mg/kg; and 30th mm at doses of 0.4 and 0.6 mg/kg. Then, the blood selenium levels gradually decreased to the near levels of control groups at 120th hours at doses 0.1 and 0,2 mg/kg, 168th hours at doses 0.4 and 0.6 mg/kg. Selenium levels in liver, kidney, spleen, heart, lung, muscle and bile started to increase at 30th min and were observed to reach the maximum levels at 1st hours in spleen, heart and lung; at 3rd hours in liver, kidney and muscle; at 9th hours in bile, following the application of selenium intramuscularly at the doses ol 0,6mg/kg. Then, the selenium levels determined to gradually decrease and they were ai the higher levels than control groups at 24th hours. No changes were observed in the selenium levels in hair, skin and toenail within the 24 hours.